On the evaluation of DHT22 temperature sensor for IoT application - Ahmad, Yasser Asrul; Gunawan, Teddy Surya; Mansor, Hasmah; Hamida, Belal Ahmed; Hishamudin, Adam Fikri; Arifin, Fatchul (IEEE, 2021)
Temperature is one of the most monitored items in many industrial and commercial applications. Internet of Things (IoT) temperature sensors are commonly small, low power, and able to measure humidity as well. Obtaining timely, accurate temperature information is critical in an IoT system. This paper aims to evaluate an IoT temperature system’s performance by comparing it with an industrial system. In this project, an IoT temperature monitoring system has been developed using a DHT22 temperature sensor and a Raspberry Pi to represent an IoT temperature monitoring system. The system is evaluated by comparing its temperature measurement with a Keithley 6517-TP industrial grade temperature probe connected to Keithley 2110 benchtop digital multimeter as the acquisition system. The IoT temperature monitoring system utilizing the DHT22 sensor provides accurate measurement up to 0.10C but a slower response in detecting temperature change. This finding would be able to provide a reference in developing an IoT system that requires temperature monitoring.